Tribological investigation on metal mating surfaces to explore real use conditions of a novel friction damper for seismic applications. (1st March 2023) - Grossi, Eleonora; Aprile, Alessandra; Zerbin, Matteo
Highlights: Tribological investigation for the development of a novel friction damper. Pin-on-Disk tests methodology set up to reproduce real use conditions. The execution of running-in stages improves friction coefficient steadiness. The interaction of steel with softer metal material decreases surfaces damage. Abstract: The seismic rehabilitation of existing buildings is a strategic goal for many countries located in high seismic risk areas of the globe. Retrofit techniques based on energy dissipation by implementing additional mechanical dampers into the structure have proved to be very efficient. Among the others, friction-based dampers have revealed to be particularly simple and cheap; nonetheless, for this kind of device, the selection of mating surfaces set a crucial point. This paper shows the experimental investigation performed for the development of a novel Friction Damper (FD) using Pin-on-Disk (PoD) tests and highlights the main tribological aspects useful for the full-scale tests. PoD tests have been set to simulate the real use condition of the device in development under the action of subsequent earthquakes. Sliding surface's material and machining processes have been selected taking into account the S355JR steel main body of the device in development, and the need of reducing the friction's abrasive component and the particle formation during sliding. The experimental campaign has been addressed to highlight the influence of surface roughness, machining processes, additional treatment, and different coupling materials on Coefficient of Friction (COF) mean value and its statistical dispersion.